Antihypertensive Drug Use in Patient With Intracerebral Hemorrhage Stroke - Luh Putu Febryana Larasanty (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2012)
Intracerebral hemorrhage (ICH) stroke is a type of stroke with the highest mortality rate, with only about 38% of patients who survived for the first year after stroke. Antihypertensive treatment one of the main therapy for reduce the mortality rate in ICH. Based on review from research study journals, peer review journals, guidelines or book about use of antihypertensive drugs in ICH stroke patient and/or hypertensive emergency, uses of nicardipine, labetalol, esmolol and enalapril can be as the first-line therapy to manage acute high blood pressure in intracerebral hemorrhage stroke if there is no contraindication or caution is present. Nicardipine, labetalol, esmolol and enalapril is four agent that reduce blood pressure in a titratable fashion and do not lead increases in intracranial pressure. Hydralazine, sodium nitroprusside and nitroglycerine can be used as alternative agent if nicardipine, labetalol, esmolol and enalapril can not be used in ICH stroke patient. Keywords: Stroke, Intracerebral Hemorrhage, Antihypertensive Agent